KENYAMANAN DAN KEPERCAYAAN KONSUMEN BLIBLI.COM BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Asyifa, Lia Siti; Rahayu, Agus (Business Education Program of Universitas Pendidikan Indonesia, 2017)
Purpose - The purpose of this paper was to be found out the influence of shopping enjoyment and consumer trust towards online purchase decision on member of Fan page Facebook Blibli.comDesign/methodology/approach – This type of research used are descriptive, verifikatif. The method used was explanatory survey with simple random sampling techniques and sample number of 165 respondents. Data analysis technique used is a path with equal tools computer software SPSS 22.Findings – shopping enjoyment and consumer trust has influenced on purchase decisions online simultaneously and partially.Originality/value - The paper provides a basis to understand the issues of purchasing decisions on member of fan page facebook Blibli.com. The difference of this study with earlier research on objects that are the variable used supporting the theory as well as the different references used by previous researchers. Keywords:Shopping Enjoyment, Consumer Trust, Purchase Decision, Purchase Decision Online Article Type: Research Paper